Mastering writing essentials - Macdonald, Andrew 1942- (Prentice Hall, 1996)
This 700+ page introduction to academic writing provides comprehensive writing instruction for ESL learners. Teaches critical thinking skills and includes effective, tested prewriting exercises and writing assignments. For advanced ESL learners.